Identification and expression profiling of the CoDof genes involved in fatty acid/lipid biosynthesis of tetraploid Camellia oleifera - Zhao, Guang; Chen, Lina; Zhang, Lin; Liao, Chancan; Wang, Jin (Frontiers in Plant Science, 2025)
IntroductionCamellia oleifera, a crucial woody oil crop in China, produces seeds with over 90% unsaturated fatty acids offering substantial nutritional value and exists predominantly as cultivated tetraploid varieties (2n=4x=60) due to its polyploid nature. The DNA-binding with one finger (Dof) transcription factor play multiple roles in plant growth, development, and abiotic stress response pathways. However, the regulatory mechanisms of Dof genes underlying fatty acids/lipids biosynthesis during seed morphogenesis in Camellia oleifera remain poorly characterized.MethodsIn this study, genome-wide identified a total of 40 members of the CoDof family with 116 alleles in tetraploid Camellia oleifera (COL-tetra).ResultsAll members possess varying numbers of highly conserved C2-C2-type zinc finger domains. Phylogenetic analysis clustered CoDof genes into nine categories, and significant divergence was observed in the expression levels of all family members across different growth and development stages of COL-tetra seeds. After physiological data determination at various levels, differential expression analysis and correlation analysis of fatty acid/lipid synthesis genes revealed that CoDof30.1 is a typical candidate nuclear-localized transcription factor which significantly highly expressed in the middle period of seed development.DiscussionOur findings not only comprehensively characterize the genomic organization of CoDof family but also propose a functional candidate for lipid biosynthesis regulation, thereby advancing molecular breeding strategies and elite cultivar selection in COL-tetra.